Pengaruh Ukuran Perusahaan, Profitabilitas, Leverage, Dan Kepemilikan Institusional Perusahaan Terhadap Nilai Perusahaan - Lani, Sufiyati (Fakultas Ekonomi, Universitas Tarumanagara, 2019)
This study aims to obtain empirical evidence on the effect of firm size, profitability, leverage, and institutional ownership of companies on firm value in manufacturing companies of consumption goods industry sectors listed in Indonesia Stock Exchange in the period 2015-2017. Research samples are 25 companies out of 42 companies data using purposive sampling method. Results of this research obtained the firm size have no effect to firm value, profitability have positive effect to firm value, leverage have no effect to firm value, and institutional ownership have no effect to firm value.